Find your strongest life : what the happiest and most successful women do differently - Buckingham, Marcus (Nashville, Tenn. : Thomas Nelson, 2009)
In this research-based primer, the author reveals the powerful key to help women draw enough strength from life to feel fulfilled, loved, successful, and in control by helping them reconnect with their purpose and giving them a starting point for change.
Keywords: Women -- Psychology; Self-actualization (Psychology).; Success